Origin of color variations of thin, nano-sized layers of volcanic cinder from the Sierra Negra Volcano of the Galapagos Islands - Debut, Alexis (2021)
Volcanic cinder, also known as scoria, is an extrusive igneous rock that forms when gas-rich magmas of basaltic or andesitic composition cool quickly. It is typically dark in color, ranging from black to red depending on its chemical composition. Sometimes fresh cinder samples show a variety of shiny metallic colors on its surface ranging from blue to gold to silver. The origin of these colors has remained unknown up to now. Cinder samples from an eruptive event occurred in October 2005 have been collected in the surroundings of the Sierra Negra volcano in the Galápagos Islands. The samples’ crystallographic structure, chemical composition, and surface morphology have been analyzed using X-Ray diffractometry (XRD), energy dispersive X-Ray spectroscopy (EDS) and a field gun emission scanning electron microscopy (SEM), respectively. Based on an extensive physical and chemical analysis, we were able to demonstrate that these colors are due to a light interference phenomenon. These results have a great potential to be used for a wide variety of purposes such as determining the temperature and composition of magma and evaluating volcanic samples for planetary studies.